Correction: Vestibular Evoked Myogenic Potential (VEMP) Triggered by Galvanic Vestibular Stimulation (GVS): A Promising Tool to Assess Spinal Cord Function in Schistosomal Myeloradiculopathy. - Júlia Fonseca de Morais Caporali; Denise Utsch Gonçalves; Ludimila Labanca; Leonardo Dornas de Oliveira; Guilherme Vaz de Melo Trindade; Thiago de Almeida Pereira; Pedro Henrique Diniz Cunha; Marina Santos Falci Mourão; José Roberto Lambertucci (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004672.].